2019
DOI: 10.2196/11701
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Depression Comorbid With Diabetes or Hypertension in Resource-Poor Settings: A Qualitative Study About User Perception of a Nurse-Supported Smartphone App in Peru

Abstract: Background Smartphone apps could constitute a cost-effective strategy to overcome health care system access barriers to mental health services for people in low- and middle-income countries. Objective The aim of this paper was to explore the patients’ perspectives of CONEMO (Emotional Control, in Spanish: Control Emocional), a technology-driven, psychoeducational, and nurse-supported intervention delivered via a smartphone app aimed at reducing depressi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(67 citation statements)
references
References 79 publications
0
66
0
1
Order By: Relevance
“…The primary barrier to engagement noted in 25 studies was users’ experience of technical issues [ 44 , 50 , 80 , 92 , 100 , 103 , 118 , 129 , 138 , 155 , 172 , 179 , 185 , 195 , 205 , 208 , 212 - 220 ], such as a mobile app crashing and shutting down unexpectedly; in 3 studies, participants did not have the resources required to use an intervention [ 171 , 221 , 222 ]. In 7 studies, participants expressed concerns over the eventual costs associated with using an intervention [ 85 , 93 , 104 , 123 , 165 , 223 , 224 ]. Costs could be related to the need for a smartphone, having internet access, or making purchases through the app.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary barrier to engagement noted in 25 studies was users’ experience of technical issues [ 44 , 50 , 80 , 92 , 100 , 103 , 118 , 129 , 138 , 155 , 172 , 179 , 185 , 195 , 205 , 208 , 212 - 220 ], such as a mobile app crashing and shutting down unexpectedly; in 3 studies, participants did not have the resources required to use an intervention [ 171 , 221 , 222 ]. In 7 studies, participants expressed concerns over the eventual costs associated with using an intervention [ 85 , 93 , 104 , 123 , 165 , 223 , 224 ]. Costs could be related to the need for a smartphone, having internet access, or making purchases through the app.…”
Section: Resultsmentioning
confidence: 99%
“…Costs could be related to the need for a smartphone, having internet access, or making purchases through the app. Usability issues formed a barrier to engaging with an intervention [ 46 , 50 , 78 , 84 , 148 - 150 , 157 , 159 , 170 , 224 - 228 ]. Examples of usability issues were difficulty finding information in an intervention [ 78 ], a time-consuming process to log in to an intervention [ 159 ], and difficulty navigating within an intervention [ 150 , 157 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of digital technology to deliver mental health interventions has been increasingly recognized worldwide [120]. There is a growing literature on interventions using smartphone applications to promote mental health, both with [121,122] or without the intermediation of a mental health professional [31]. Our study adds to the literature by testing whether an app providing an intervention package, including CBT, psychoeducation, nutrition, physical activity, and social support, can promote maternal and child health and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…In Lima, the study was conducted in primary health care centers from the social security network and outpatient services from three hospitals from the Ministry of Health network. A pilot study found nurses in Peru were overwhelmed with the number of tasks assigned to them, and, with a few exceptions, were not motivated to invest time in additional responsibilities [17]. This was a likely barrier to implementation so the research team decided to hire full-time nurses to conduct the intervention.…”
Section: Study Setting/designmentioning
confidence: 99%